2015
DOI: 10.1021/acs.est.5b02691
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Mercury Exposure of Piscivorous Birds and Sport Fish Using Prey Fish Monitoring

Abstract: Methylmercury is a global pollutant of aquatic ecosystems, and monitoring programs need tools to predict mercury exposure of wildlife. We developed equations to estimate methylmercury exposure of piscivorous birds and sport fish using mercury concentrations in prey fish. We collected original data on western grebes (Aechmophorus occidentalis) and Clark's grebes (Aechmophorus clarkii) and summarized the published literature to generate predictive equations specific to grebes and a general equation for piscivoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Back-transformed standard errors were estimated using the delta method (Seber 1982). In order to standardize the relative risk estimates, the least squares mean prey fish THg concentration in each grid was converted to the equivalent avian blood THg concentrations using the global equation from Ackerman et al (2015), which synthesized seven different study’s equations (Eq. 3).…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Back-transformed standard errors were estimated using the delta method (Seber 1982). In order to standardize the relative risk estimates, the least squares mean prey fish THg concentration in each grid was converted to the equivalent avian blood THg concentrations using the global equation from Ackerman et al (2015), which synthesized seven different study’s equations (Eq. 3).…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…(Ackerman et al, 2015) ln0.2emfalse(italicBird0.2emitalicBlood0.2emTHgwwfalse)=1.788+0.6182lnfalse(normalPrey0.2emitalicFish0.2emTHgwwfalse)…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a percent moisture of 79% (see Eagles-Smith et al, 2008) was assumed to convert μg/g dw to μg/g ww. (eq 3) ln(FemaleBirdBlooditalicTHgnormalμggww)=1.0734×ln(EggitalicTHgnormalμggfww)+0.8149 (R 2 = 0.95; Ackerman et al, 2016a) (eq 4) ln(FemaleBirdBlooditalicTHgnormalμggww)=0.6182×ln(PregFishitalicTHgnormalμggfww)+1.788 (Ackerman et al, 2015) (eq 5) ln(BlooditalicTHgnormalμggww)=1.080×ln(BirdMuscleitalicTHgnormalμggdw)-1.024 (R 2 = 0.90; Eagles-Smith et al, 2008) c Moisture content from the study was used if reported. If it was not reported, a moisture content of 67% in liver, 75% in eggs, 70% in muscle, and 79% in blood was used (Eagles-Smith et al, 2008).…”
Section: Figurementioning
confidence: 99%
“…(eq 4) ln(FemaleBirdBlooditalicTHgnormalμggww)=0.6182×ln(PregFishitalicTHgnormalμggfww)+1.788 (Ackerman et al, 2015)…”
Section: Figurementioning
confidence: 99%